Mesenteric panniculitis: therapeutic aspects in the light of a clinical case - GOREA, Alexandru; STOICA, Mihaela; SCORPAN, Anatolie; SARBU, Oxana; ISTRATI, Valeriu (One Health & Risk Management, 2022)
Introduction: Mesenteric panniculitis is a rare medical condition. Its incidence is between 0.16% - 3.4%. The small number of cases of PMN and the ignorance of its causes, pathogenesis and treatment significantly affect the prognosis of the disease.Materials and methods: An analysis of the literature and the case of patient R, aged 47, who is admitted to IMSP, is presented.Results: Accusations: peri-umbilical pain, marked physical asthenia and significant weight loss. In the left abdominal flank, a tumor of 9.0 x14.0 cm was palpated, soft as consistensy, elastic, sensitive to palpation, fixed to the deep planes. Clinical examination and abdominal CT examination led to the diagnosis of mesenteric panniculitis. Drug treatment with NSAIDs and corticosteroids had a favorable outcome, confirming the autoimmune etiology of PM.Conclusions. Mesenteric panniculitis is a rare pathology and its diagnosis is difficult to establish. The drug treatment with NSAIDs and corticosteroids can lead to good and lasting clinical results.